Analisis Keamanan Aplikasi Café Egg And Butter Berbasis Android Menggunakan Mobile Security Framework (MobSF) - Fadillah, Adhitya Rizkyawan; Primajaya, Aji; Carudin, Carudin (Jurnal Ilmiah Wahana Pendidikan, 2026)
Mobile application security is a crucial aspect of software development, particularly on the Android platform, which has a broad user base and an open-source nature. This study aims to analyze the security level of the Android-based Café EggAndButter application using the Static Application Security Testing (SAST) approach through the Mobile Security Framework (MobSF) tool. The main focus of this research is to determine the security score, identify potential vulnerabilities, and assess the application’s security risk level. The analysis result show that the application received a Security Score of 37/100 with Risk Rating Grade of C, indicating a relatively high security risk. Three major vulnerabilities were found: Exported Activity without access control, Insecure Logging, and unencrypted storage of login tokens. Additionally, the use of weak cryptographic algorithms (MD5 and SHA-1) and two requests for dangerous permissions were identified. However, no vulnerabilities related to SSL of malicious domains were found. In conclusion, the application still has several weaknesses that need to be addressed, especially in component management and data protection